Sacred Art from the Frontline: The Iconography and Symbolism of the Contemporary Ukrainian Art Project “Holy Icons on Ammunition Boxes” - Andriy Lesiv (Anastasis: Research in Medieval Culture and Art, 2024)
The paper is highlighting the unique phenomenon of modern Ukrainian sacred art – holy icons painted on panels made of ammunition boxes brought from the war zone in Ukraine. The aim of this paper is to conduct a comprehensive study of the project “Holy Icons on Ammunition Boxes” from the point of view of art history and social culture; to understand the prerequisites for the appearance of the art project “Holy Icons on the Ammunition Boxes” and its functions as social and volunteer project; to carry out an art analysis of separate holy icons and icon painting cycles of this art project. Several interviews with the creators of the project – artists Oleksandr Klymenko and Sofia Atlantova – were conducted, based on which the necessary conditions for the creation of holy icons, their symbolism, iconography, and social function (which is manifested in the support of the First Voluntary Mobile Hospital named after Mykola Pirogov) were analysed. The project “Holy Icons on Ammunition Boxes” carries an important function of unification and fusion: stitching together the rear and the frontline. Its symbolism is based on the antithesis of death and life, the transformation of death into life, not only on a symbolic level, but also literally since all funds from the holy icons’ sales are directed to saving the lives of wounded Ukrainian soldiers and civilians. Weapons, which are originally instruments of death, acquire the opposite symbolic qualities, and become sacred artifacts. The article analyses both the artistic features of the project and its social function, which is no less important.